The Ophelia cut : a novel - Lescroart, John T. (Lescroart, John T. Dismas Hardy novel, 2013)
"Defense attorney Dismas Hardy returns to defend a close friend against murder charges in New York Times bestselling author John Lescroart's most suspenseful and intricately plotted novel to date"--